Experimental study of the adsorption of 2-Chloroacetophenone at the air-environmental water interface - Hao, Shangpeng; Liu, Xuefeng; Sun, Chao; Zhang, Yuanpeng; Gao, Runli; Wang, Haitao; Wang, Xiaolu (Frontiers in Environmental Science, 2022)
The widespread surface of the air-water interface plays a crucial role in the partitioning processes between the atmosphere and the hydrosphere. As one of the prime CWAs (Chemical Warfare Agents) abandoned by Japanese, the unfound 2-Chloroacetophenone posed a severe threat to the Chinese people. In this study, the interface partition constant of 2-Chloroacetophenone was obtained by measuring the mass uptake vapor on different environmental water films with various thicknesses. The surface tension, dissolved organic matter, and salinity of the environmental samples were analyzed. The KAI of 2-Chloroacetophenone in pure water, river water and sea water samples at 288K were 1182.2±49.9, 1606.6±101.3 and 408.9±18.3, respectively. Surface adsorption is the predominant mechanism. The results also indicate that the adsorption partitioning ability of 2-Chloroacetophenone at the air/water interface was negatively correlated with surface tension. 2-Chloroacetophenone is more likely to adsorb at the gas/water interface with lower surface tension.